The Palgrave handbook of policy transfer in vocational education and beyond - Barabasch, Antje [Herausgeber]; Bohlinger, Sandra [Herausgeber]; Wolf, Stefan [Herausgeber] (Palgrave Macmillan, 2026)
"This handbook provides a comprehensive overview of the field of policy transfer in education, with a particular focus on technical and vocational education and training (TVET), adult education, professional and higher education. Bringing together contributions from around the world, the chapters indicate how policy transfer should be embedded in regional and cultural contexts, according to established knowledge as well as emerging perspectives. The book will be a must-read for researchers, policymakers and practitioners working in all areas of education relating to labour market skills, who are aiming for an improved understanding of the successes and failures of policy transfer initiatives in TVET and higher education." (Publisher, BIBB-Doku)
E-Book für BIBB-Mitarbeitende über die Bibliothek erhältlich.
Keywords: S 1 Stufen der Berufsbildung; S 2.3 Berufsbildungspolitik; T 1.5 International vergleichende Berufsbildungsforschung; 370; Berufsbildung; Berufsbildungspolitik; Transfer; Berufsbildungssystem; Erwachsenenbildung; Hochschulbildung; Internationaler Vergleich; Vergleichende Berufsbildungsforschung